Frontiers in Photonics Spot Light - Anvari, Bahman; De Angelis, Costantino; Huang, Shujuan; Litchinitser, Natasha; Poon, Ting-Chung; Scalari, Giacomo; Richards, Bryce S.; Peccianti, Marco (Frontiers in Photonics, 2022)
Recognizing remarkable achievements and innovations is an important mission in scientific dissemination. The editors of Frontiers in Photonics would like to acknowledge and give visibility to some of the best recent research outputs and to their authors in this spot-light review.